The Digital Scoring of Pencak Silat Matches as a Supporting Application for Event Organizer Entrepreneurs - Ashabul Khairi; Asmar Yulastri; Ganefri Ganefri; Ambiyar Ambiyar; Fadillah Fadillah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
An event Organizer is the manager of an activity or event that is held to make a profit for the event organizer and those present at the time the activity takes place. The Event Organizer service business requires creative and innovative people who are rich in ideas or concepts and have a wide network of friends. Event Organizer Entrepreneurs do not require a special place such as an office or special workspace but can be done by working from home, utilizing a PC or Laptop, and optimizing communication and presentation skills to prospective clients, even the Event Organizer business does not require a large initial capital. The main goal of the research is to produce a product that can realize a quality match with a transparent digital scoring system. In addition, this digital scoring application is a supporting application in starting an entrepreneur in the Event Organizer field because this application can be rented out in every Pencak Silat championship that requires this assessment application. This design is based on the flow chart of Nasir's research methodology which includes; the identification of problems, formulation of problems, determining the purpose of benefits and limitations, preliminary survey-observation, literature study. The design uses the waterfall model, a classical model that is systematic, sequentially, step by step through which it must wait for the completion of the previous stage. Validity Test The digital scoring application is in the very valid category.